2017
DOI: 10.11604/pamj.2017.27.235.13121
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of human immunodeficiency virus, hepatitis B and C viruses among haemodialysis patients in two newly opened centres in Cameroon

Abstract: IntroductionHaemodialysis (HD) patients are potentially susceptible to infection with blood borne viral agents especially; Human Immunodeficiency Virus (HIV), hepatitis B (HBV) and hepatitis C Viruses (HCV), compared to the general population. We described their epidemiology in two newly created haemodialysis units in Cameroon: the Buea and Bamenda haemodialysis centres.MethodsA cross sectional study: included were patients who had spent at least three months in haemodialysis. HBV, HCV and HIV serologies were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…None of these following parameters age, sex, type of initial nephropathy, vascular approach, the concept of blood transfusion and duration of dialysis was not statistically significant (p > 0.5) in hemodialysis patients with HBsAg positive compared to seronegative HBsAg patients. This result is similar to those of LUMA et al [15] in Cameroon and KOUASSI-M'BENGUE et al [5] in Côte d'Ivoire. With regard Open Journal of Medical Microbiology to blood transfusion, it should be pointed out that this is one of the essential adjuvant therapeutic components in the management of hemodialysis in Togo.…”
Section: Discussionsupporting
confidence: 92%
“…None of these following parameters age, sex, type of initial nephropathy, vascular approach, the concept of blood transfusion and duration of dialysis was not statistically significant (p > 0.5) in hemodialysis patients with HBsAg positive compared to seronegative HBsAg patients. This result is similar to those of LUMA et al [15] in Cameroon and KOUASSI-M'BENGUE et al [5] in Côte d'Ivoire. With regard Open Journal of Medical Microbiology to blood transfusion, it should be pointed out that this is one of the essential adjuvant therapeutic components in the management of hemodialysis in Togo.…”
Section: Discussionsupporting
confidence: 92%
“…It is recommended to analyze HBV-DNA annually and biopsy from liver [ 19 ]. An additional study done in Cameroon reported that the frequency of HBs Ag and HCV Abs infections in HD patients was 10.6% and 19.2%, respectively [ 20 , 21 ]. In India, out of 262 patients, 88 (33.5%) were found to be having HCV infection, 4 (1.5%) were found to be positive for HBsAg and dual infection was observed in 2 (0.8%) patients [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bruggeman et al [58] discussed the mechanism of viral replication in CKD patients, implying viral infections as a comorbid condition in CKD. The seroprevalence of HIV, hepatitis B surface antigen and hepatitis C virus was reported to be high in hemodialysis centers in Cameroon as well [40,41].…”
Section: Discussionmentioning
confidence: 99%